Ideas previas, esquemas alternativos, cambio conceptual y el trabajo en el aula - García Hourcade, J. L.; Rodríguez de Ávila, C. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
This paper contributes to clarify concepts such as those of previous knowledge, alternative frameworks and conceptual change, usually conveying very different meanings.